Effect of addition of inulin and fenugreek on the survival of microencapsulated Enterococcus durans 39C in alginate-psyllium polymeric blends in simulated digestive system and yogurt - Babak Haghshenas (Asian Journal of Pharmaceutical Sciences, 2015)
The use of biopolymers for probiotic microencapsulation has been investigated in this paper. The objectives are to enhance its survival rate, colonic release, and stability of these probiotic cultures in digestive condition during storage time. Nine types of biopolymers (alginate-psyllium) blend with different concentration of prebiotic; (inulin or fenugreek) were used as candidate for microencapsulation matrix. One strain of probiotic candidates, namely; Enterococcus durans 39C was used in this study. The microencapsulation of this strain with the respective polymer blend was performed by using a simple extrusion method. All blend of formulations have recorded high encapsulation efficiency at value >98%. The survival rate of viable probiotic cells under simulated digestive conditions was also high with value above 47% as compared to non-microencapsulated cells. These nine gel formulations also displayed the high survival rate of viable probiotic cells during storage time (28 d). Their release occurred after 2 h in colonic condition and sustained until 12th h of incubation period. An increase of prebiotic effect value added was observed in incorporated inulin and fenugreek formulations. In short, this study revealed that a new herbal-based psyllium and fenugreek polymers have suitable potential as a matrix for probiotic microencapsulation.